Haemoglobin genotype, ABO and rhesus blood group pattern among students of Bamidele Olumilua University of Education, Science and Technology Ikere, Ekitis state, Nigeria - Ajayi, David O.; Omon, Emmanuel A.; Orekoya, Adefolurin; Oluwayomi, Oludare (International Journal of Research in Medical Sciences, 2022)
Background: The two most significant blood group systems of clinical importance are ABO and rhesus. An essential blood component that determines haemoglobinopathies is haemoglobin genotype. The aim of the study was to determine the distribution of haemoglobin genotypes, ABO and rhesus blood groups pattern among students of Bamidele Olumilua University of Education, Science and Technology Ikere (BOUESTI), Ekiti state. Methods: Two thousand (2,000) samples comprising 840 (42%) males and 1,160 (58%) females were recruited for this study. The ABO blood group was determined using tile method, while the haemoglobin genotype was determined using haemoglobin electrophoresis. Data analysis was done using simple percentage and Chi square test. Results: The results obtained showed that out of the two thousand subjects that participated in this study, 1,448 (72.4%) of the subjects had HbAA, 452 (22.6%) had HbAS, 72 (3.6%) had HbAC, 20 (1%) had HbSS and 8 (0.4%) had HbSC. The distribution of ABO blood groups of the subjects were; blood group O (53.6%), blood group B (26.6%), blood group A (17.8%) and blood group AB (2.0%). Furthermore, 96.0% of the subjects were rhesus ‘D’ positive, while 4.0% were rhesus ‘D’ negative. There was no significant difference (p>0.05) in the haemoglobin genotypes and ABO blood groups of the subjects with respect to age and sex. Conclusions: The study concludes that the distribution of ABO blood group in the study population was given by O>B>A>AB, while the genotype was given by AA>AS>AC>SS>SC respectively. Continued haemoglobin genotype test and premarital counselling of potential couples is highly recommended.